Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.14569/ijacsa.2011.020805
|View full text |Cite
|
Sign up to set email alerts
|

Some Modification in ID-Based Public key Cryptosystem using IFP and DDLP

Abstract: Abstract-In 1984, Shamir [1] introduced the concept of an identity-based cryptosystem. In this system, each user needs to visit a key authentication center (KAC) and identify him self before joining a communication network. Once a user is accepted, the KAC will provide him with a secret key. In this way, if a user wants to communicate with others, he only needs to know the "identity" of his communication partner and the public key of the KAC. There is no public file required in this system. However, Shamir did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Applying Meshram and Meshram attacking method [14] to the proposed system, it may be noted that center's secret information may be disclosed.…”
Section: Security Analysis and Discussionmentioning
confidence: 99%
“…Applying Meshram and Meshram attacking method [14] to the proposed system, it may be noted that center's secret information may be disclosed.…”
Section: Security Analysis and Discussionmentioning
confidence: 99%
“…Since Pang et al 10 found out two type of deadlock problems in Meshram et al 26 and removed by some modification in IBC technique using GDLP and IFP 10,20‐22,27 and also discussed security of the technique without given formal security proof. But in cryptographic technique‐based manuscript, formal security analysis, and security proof are required with proper justification.…”
Section: Review Of Pang Et Al Ibcmentioning
confidence: 99%
“…GDLP along with IFP 10,20‐22,27 are used in this proposed IBC. The technique has divided into four sub‐algorithms, including Setup, Extraction, Encryption, and the Decryption.…”
Section: The Propose Improved Ibcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the scheme is inefficient in that a plain-text message is encrypted bit-by-bit and hence the length of the output ciphertext becomes long. [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] have been proposed. But in these schemes, the public key of each entity is not only an identity, but also some random number selected either by the entity or by the trusted authority.…”
Section: Introductionmentioning
confidence: 99%